Factors associated with Missed Opportunities for Vaccination among children in the first year of life at a tertiary health facility in Lagos - Kehinde OA; Kuyinu YA; Odusanya OO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Low vaccination rates in children remain a major problem in resource-poor areas of the world. Missed opportunities for vaccination may be one of the important contributors to the menace. Objectives: To determine the prevalence of missed opportunities for vaccination and identify factors associated with this among Nigerian children in the first year of life. Methods: The study was a descriptive, cross-sectional study of children who were recruited consecutively and data were obtained using a questionnaire. Results: Two hundred and fifty-six children were recruited. The prevalence of missed opportunities for vaccination was 11.3%. Gender (p = 0.04) and parental socioeconomic status (p = 0.008) were significantly associated with missed opportunities for vaccination. Non- availability of required vaccines and reluctance to open a multi-dose vial of vaccine caused MOV in 55.5% and 51.8% of children respectively. The evaluation of vaccination status among subjects who were not fully vaccinated by health workers was low at 18.3%. Conclusion: The rate of missed opportunities for vaccination was low. Educating caregivers and encouraging health workers to evaluate the vaccination status of children at every contact with a health facility may reduce the prevalence of missed opportunities for vaccination.